Pengaruh Globalisasi terhadap Keamanan Manusia: Dampak Benih Rekayasa Genetika terhadap Ketidaktahanan Pangan - Aryani, Maria Indira (Global and Policy Journal of International Relations, 2014)
ABSTRACTHuman security is a concept driven from national security. Human security is a concept whichemphasize in the protection of individuals. As this concept is affected by globalization, so doesthe concept of human insecurity. This writing, particularly, discuss about food insecurity offarmers and global citizens, as one component of human security, caused by GeneticallyModified Organism (GMO). GMO is protected by the patent law and intellectual and propertyrights and this situation limits farmer’s access to reach food security. GMO also endangershuman health from its transgenic mutation. This research is focused between 1996, when GMOis first commercialized, to 2014.Keywords: human security, food security, food insecurity, genetically modifiedorganism.DOI:https://doi.org/10.33005/jgp.v2i02.2064